Quality of Public Service in the Middle of Covid-19 Pandemic at the Office of Population and Civil Registration Gowa District - Irham, Irham; Hardiyanti, Sartika Dwi (Budapest International Research and Critics University, 2021)
This study was compiled to find out how the quality of public services at the Population and Civil Registration Office during the Covid-19 pandemic in Gowa Regency. This study used descriptive qualitative method. Collecting data through observation, interviews, documentation, and literature study. Service quality in this study focused on the dimensions of Realibility, Responsivness, Tangible, Assurance, and Empathy. The results showed that the quality of public services at the Office of Population and Civil Registration, Gowa Regency, which was carried out in the midst of the Covid-19 pandemic, was considered quite good. Although public services are carried out with limitations due to the COVID-19 pandemic, the community is still well served. The ability of employees who serve well even with strict health protocols, are responsive to providing information to the public, facilities and infrastructure that conform to health protocols but still make the community comfortable, guarantee clear time and costs, and friendly and courteous service. Public services are carried out with strict health protocols, carried out online and offline so that people get quality services.